Hydrogen in Nickel: Hydride or Miscibility Gap? - Movchan, D.N.; Teus, S.M.; Mogilny, G.S.; Gavriljuk, V.G. (Металлофизика и новейшие технологии, 2013)
Using low temperature X-ray diffraction, the phase transformations in the hydrogen-saturated nickel are studied. At the hydrogen degassing, its content in nickel decreases down to H/M ratio of about 0.65. The further decreasing of hydrogen content leads to the two-phase separation, notably, hydrogen-rich and hydrogen-depleted solid solutions with permanent hydrogen concentrations existing while the hydrogen-rich phase does not disappear. Based on the Gibbs’ idea about two types of precipitation reactions and available experimental data, it is concluded that, in fact, the so-called Ni-hydride is a hydrogen-rich solid solution, which appears because of miscibility gap in the Ni—H system. At higher hydrogen contents beyond the crown, hydrogenrich phase exists in the wide concentration range as a supersaturated hydrogen solid solution in nickel, which is also incorrectly interpreted as Nihydride.